x+6x-4x+27=0

Simple and best practice solution for x+6x-4x+27=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+6x-4x+27=0 equation:


Simplifying
x + 6x + -4x + 27 = 0

Reorder the terms:
27 + x + 6x + -4x = 0

Combine like terms: x + 6x = 7x
27 + 7x + -4x = 0

Combine like terms: 7x + -4x = 3x
27 + 3x = 0

Solving
27 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 3x = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 3x = 0 + -27
3x = 0 + -27

Combine like terms: 0 + -27 = -27
3x = -27

Divide each side by '3'.
x = -9

Simplifying
x = -9

See similar equations:

| 8w-10w=14 | | 7*-4y=-7 | | 4u^2-10u+4=0 | | 5(5/2-3/4)-6y=19 | | 13=10+3j | | 5-1/2(m-6)=4 | | 3x+2x+1(2x+3x)=888 | | 1.3+0.8+3= | | 25(12n)+5n=5.40 | | 5(x-1)-3k=-2(k+3)-7 | | 4.2x=-1 | | m+4t=36 | | -3x+2(6+2x)=-6 | | 2mn+3y+4mn+6= | | 1.7x=5.2 | | 5-10x=-1(3-2x) | | 1.30=60+50 | | -2(r+3)=-27 | | 4.1x=4.2 | | Log(5x)-log(8)=1 | | 6x+6x(4x-2)+(4x-2)= | | f(x)=x^3-4x^2+x-10 | | -5u^2+u+4=0 | | 3(x+3)-5x=12-(6x-7) | | 2m+3t=32 | | 5/6x1/7 | | 4n^2-4n-24=0 | | ln(4x-1)=9 | | x+23+3x=14-3x-19 | | 6x+2x-9=39 | | x^2+1.8x-.16002=0 | | 3x-34=7(x-2) |

Equations solver categories